Do Skills Matter in Influencing Employment for People with Disabilities? Exploring the Role of ICT Skills and Education - Elita Pertiwi; Vierra Citra Dewi Suchendar; Raden Muhamad Purnagunawan; Ferry Hadiyanto (Jurnal Ketenagakerjaan, 2025)
This study investigates how education and information and communication technology (ICT) skills influence the likelihood of employment among people with disabilities (PWD) in Indonesia. Drawing on data from the 2022 National Socioeconomic Survey (SUSENAS), I estimate a probit model to identify the key factors affecting labor market inclusion for PWD. The results show that both higher levels of education and ICT proficiency significantly increase the probability of employment. In contrast, being female, caring for young children, living in urban areas, or experiencing severe disability are all associated with lower employment odds. Notably, the relationship between education and employment is non-linear, with positive effects emerging only beyond a certain threshold of schooling. These findings underscore the importance of targeted interventions, particularly in digital literacy and education access, to improve labor market outcomes for people with disabilities. The results offer timely policy implications for promoting inclusive economic participation in line with Indonesia’s commitment to the Sustainable Development Goals.